Psychosocial Impact of the COVID-19 Crisis on Frontline Social Care Workers in Romania: Preliminary Findings - Goraș, Carmen Elisa (European Journal of Sustainable Development, 2025)
The pandemic exposed systemic vulnerabilities and intensified indirect trauma among social care workers, a group often marginalised in disaster planning. This article reports the preparatory stage of a doctoral study on Bucharest frontline workers, using a sequential mixed-methods design. For instrument adaptation and validation, it leverages the Erasmus+ CARES national dataset (n=296) to calibrate a culturally adapted Romanian ProQOL v5 with sensitivity to masked burnout. Preliminary findings indicate elevated secondary traumatic stress and high compassion satisfaction, with burnout near the normative mean yet suggestive of masking where organisational support is weak. The forthcoming qualitative phase (pending ethics approval) will explore coping, peer/institutional support, and organisational resilience. Framed within a hazard–vulnerability perspective, the study addresses an evidence gap and informs crisis-sensitive policy on trauma-aware training, reflective supervision, and digital competence. Keywords: social care, COVID-19, psychosocial resilience, burnout, disaster response, ProQOL, Romania, secondary trauma